Coal mine disaster management robot using IoT technology - BhaskarPhani Ram, G; L. Koteswara Rao, Dr; Mahammad, Eliyaz; Bhanuchander, A (International Journal of Engineering and Technology, 2018)
One of the current trends in technology is an IoT. IoT stands for Internet of Things. It is interpreted as the communication between devices using IP address. Usage of IoT technology in coal mines reduces the number of untoward incidents. Rescue operation in coal mine deals with the risky mission. The work force inside the mine doesn’t know some explosions taking place in the proximity of mines. The rescue team also cannot understand the conditions inside the mine. The environmental parameters include toxic gases, excessive temperature, Methane leakage as well as the Oxygen. Information from the deployed sensor is transmitted to the control room through Wi-Fi. In order to address the problems in real life conditions prevailing inside the coal mine, we propose a new method to extract the related information and process the same to alert the people who are working in the vicinity of the mine. For this purpose, a framework is designed using a robotic machine integrated with the raspberry pi3 version. A camera is used in the robot so that the live video is transmitted to the Control room. A cooling fan is deployed to reduce the temperature whenever the value exceeds the threshold level. The workers get an alarm through buzzer whenever any hazardous gas is detected. The robot is controlled by means of navigation buttons, which are in turn managed internally by web server.